Philosophy of Education: Main Methodological Vectors of Moulding the Person of the Future in Higher Education - Galyna Berehova (International Society of Philosophy and Cosmology, 2017)
The paper discusses the main methodological vectors of the world outlook moulding of the person of the future in higher school required with time and defined with the state of the modern higher education in Ukraine, external and internal social and economic, political and cultural processes. The necessity of moulding a new (modern) practical world outlook of the young person in higher school, - the world outlook, which would embrace professional activity wider, joining in harmony the general values of the social system, is confirmed. The strategic approaches to the educational-and-bringing up system of higher educational establishments are outlined, the main methodological vectors of moulding the world outlook of the person of the future in higher school are determined. The first of such vectors is the correlation of moral grounds of our modern society (and of the personality in it) with the polyphony of global transformations, and thus taking into consideration the constant changes in the moral status of the modern young person in the contemporary educational spaciousness as the result of influence of general ethical processes in the world (social constructivism, cultural determinism, the negation of the individual identity, non-acceptance of traditionalism, the negation of the universalism of ethical principles, unrecognition of the transcendental origin of ethical norms). The second vector of moulding the world outlook of the person of the future is the humanization and humanitarization of higher school, which can, in the unity of synergetic character, help the humankind move away from the consumer's attitude to the nature and society. It is mentioned that the humanization and humanitarization of higher education can be deepened by means of the humanitarian disciplines which give the whole idea about the person-nature-society and the sense of the person's existence, reached by regulating the richness of content of the educational material directed to education of love for mankind and nature and social and pedagogical result via imbibing the whole educational-and-bringing up environment with an equal dialogue with a teacher loving mankind. The third vector of moulding the world outlook of the person of the future is a moral philosophy as the way of enrichment of life experience, widening of the personality's moral consciousness and bringing up "all the human in the personalit", and also a methodological landmark of the whole modern educational spaciousness and the grounds of the valuable-normative model of the world outlook of the person of the future. Much attention is given to the constant necessity of elaboration of new concepts of the philosophy of education in connection with the always changing world and an urgent need to teach and educate new generations - people of future, able to solve global problems of the mankind all the time.